Supplementation of exogenous phytohormones for enhancing the removal of sulfamethoxazole and the simultaneous accumulation of lipid by Chlorella vulgaris. (June 2023) - Yang, Lei; Vadiveloo, Ashiwin; Chen, Ai-Jie; Liu, Wen-Zhu; Chen, Dong-Zhi; Gao, Feng
Graphical abstract: Highlights: Exogenous GAs promoted the metabolism of SMX by C. vulgaris . When the GAs dose reached 50 mg/L, 91.8 % of SMX was removed. GAs promoted the production of lipid by microalgae under antibiotic stress. GAs promoted C. vulgaris to increase antioxidant enzyme activity under SMX stress. Transcriptome analysis revealed the molecular mechanism of GAs action. Abstract: In this study, the phytohormone gibberellins (GAs) were used to enhance sulfamethoxazole (SMX) removal and lipid accumulation in the microalgae Chlorella vulgaris. At the concentration of 50 mg/L GAs, the SMX removal achieved by C. vulgaris was 91.8 % while the lipid productivity of microalga was at 11.05 mg/L d -1, which were much higher than that without GAs (3.5 % for SMX removal and 0.52 mg/L d -1 for lipid productivity). Supplementation of GAs enhanced the expression of antioxidase-related genes in C. vulgaris as a direct response towards the toxicity of SMX. In addition, GAs increased lipid production of C. vulgaris by up-regulating the expression of genes related to carbon cycle of microalgal cells. In summary, exogenous GAs promoted the stress tolerance and lipid accumulation of microalgae at the same time, which is conducive to improving the economic benefits of microalgae-based antibiotics removal as well as biofuel production potential.